Green Infrastructure and Integrated Optimisation Approach Towards Urban Sustainability: Case Study in Altstetten-Albisrieden, Zurich - Yingying Jiang; Sacha Menz (Land)
In light of the challenges confronting urban areas due to increasing populations and spatial constraints, urban green infrastructure is vital for fostering environmental balance, enhancing community well being, and promoting sustainable urban development. This situation underscores the necessity for strategies that reconcile the escalating demand for constructed environments with the enhancement of urban green infrastructure in urban areas. This study seeks to empirically investigate an integrated spatial analysis approach that synthesises the quality of urban green infrastructure and land characteristics by incorporating diverse perspectives, utilising the Altstetten-Albisrieden district of Zurich as a case study. It systematically evaluates factors including development density, green surface coverage, leaf area, green ratio and connectivity, and the accessibility of public green spaces within the studied district. A 10-m rectangular grid was employed to visualise and integrate the evaluation results from different perspectives. Furthermore, clustering algorithms were utilised to generate spatial patterns indicative of unique land characteristics. By comparing the results from various clustering algorithms, this study adopted the fifteen clusters derived from the K-Means method, employing radar charts to describe the characteristics of each cluster, and partitioned the district into five zones to provide recommendations regarding the provision and optimisation of urban green infrastructure within the district. Ultimately, it highlighted the necessity of increasing community gardens and green spaces in densely built areas and leveraging existing structures to augment vegetation and plant life for the enhancement of ecological benefits.